Fecundity, Fertility and The Formation of Human Capital. Issue 618 (2nd February 2018) - Klemp, Marc; Weisdorf, Jacob
Abstract: Exploiting a genealogy of English individuals living in the 16th to the 19th centuries, this study shows that lower parental reproductive capacity positively affected the socio-economic achievements of offspring. Using the time interval between the date of marriage and the first birth as a measure of reproductive capacity, we find that parental fecundity positively affected the number of siblings and that children of parents with lower fecundity were more likely to become literate and employed in skilled and high-income professions. This suggests there was a trade-off between child quantity and quality in England during the industrial revolution, supporting leading theories of the origins of modern economic growth.